Early Signs of Memory Impairment among Multiple Sclerosis Patients with Clinically Isolated Syndrome - Theodora Panou; Vasileios Mastorodemos; Efrosyni Papadaki; Panagiotis G. Simos; Andreas Plaitakis (Behavioural Neurology)
The study investigates primary and secondary verbal memory and motor/executive functions (response inhibition and strategy shifting ability) in multiple sclerosis (MS) patients with clinically isolated syndrome (CIS). We studied 44 CIS patients and compared them to 49 patients with relapsing remitting MS (RR-MS) displaying mild disability and to a large cohort of age- and education level-matched healthy volunteers (n = 230). Results showed that both CIS and RR-MS patients evidenced a disproportionate impairment in the immediate and delayed recall of the second (as compared to the first) of two short narratives of the Logical Memory WMS-III subtest, and reduced performance on the Memory for Digits-Forward. Performance of either group on the executive tasks was not impaired, showing evidence of a reversed speed-accuracy trade-off. Illness duration emerged as a significant predictor of memory and executive task performance. Clinical, psychoemotional, and brain imaging findings were also examined as potential correlates of memory deficits and disease progression among CIS patients. These findings may signify early-onset decline of specific cognitive functions in CIS, which merits regular follow-up assessments and monitoring of psychoemotional adaptation and everyday functioning.